Health Equity in the Era of Free Trade Agreements: A Scoping Review of Mechanisms, Evidence, and Policy Options - Bera, Om Prakash; Venkatesh, U; Satapathy, Deepankar; Singh, Arshdeep; Chandge, Mokshada (Indian Journal of Community Health, 2025)
Background: Modern free trade agreements (FTAs) extend beyond tariffs to include intellectual property (IP), investment rules, and regulatory standards that influence social determinants of health and equity. Understanding these mechanisms is critical for safeguarding public health. Aims & Objectives: To synthesise evidence on the health equity implications of FTAs and identify priority policy measures for protecting vulnerable populations. Methods: A scoping review was conducted in accordance with PRISMA-ScR, covering peer-reviewed and credible grey literature in English up to 31 December 2024. Studies analysing bilateral, regional, or mega-regional FTAs with outcomes linked to health or equity were included. Thematic synthesis was organised around three predefined pathways. Results: Fifty-seven studies met inclusion criteria. TRIPS-plus and investor–state dispute settlement provisions consistently constrained access to medicines and deterred public-health regulation, with stronger adverse effects in low- and middle-income countries. Trade-driven food system shifts increased exposure to ultra-processed products, contributing to noncommunicable disease risks. Employment and environmental benefits were observed in select contexts, but impacts were uneven. COVID-19 revealed heightened equity challenges related to vaccine access and IP rules. Conclusion: FTAs shape structural conditions that influence health equity. Embedding health impact assessments, preserving TRIPS flexibilities, and protecting regulatory space are essential to ensure trade integration supports universal health coverage and the Sustainable Development Goals.